Unravelling the genetic characteristics and demographic history of human populations in diverse environments across North Asia and South America - Ghosh, Amit Gourav (Nanyang Technological University, 2023)
The vast regions of North Asia and South America harbour diverse populations, often living in extreme environments. Genetic characteristics and the demographic history of the populations of the two regions remain understudied primarily because of the underrepresentation of the populations in large-scale whole-genome studies and public databases. To shed light on the genetic characteristics and demographic history of the populations, I analysed whole-genome sequencing data of 1537 individuals from 140 populations. The results show that the North Asian and South American populations consisted of 6 and 4 genetic ancestries, respectively, with complex episodes of admixtures. Demographic history analyses revealed the influence of the Neolithic revolution and past climate change in the decline of the Kets in North Asia. Demographic history analyses also revealed that the earliest settlers reached South America and underwent simultaneous population splits 14,000 years ago as they settled and isolated in different geographic regions to give rise to the contemporary regional population structure. I highlight the case of the endangered Patagonian population, Kawésqar, who migrated the longest distance since modern humans moved out of Africa. Such dramatic migration coupled with environment-mediated isolation led to high homogeneity and severe loss in immune gene (HLA genes) diversity, making them vulnerable to unencountered pathogens. Since indigenous populations in South America inhabit harsh and environmentally divergent regions, I show that such populations underwent differential genetic adaptations to survive such conditions and associated lifestyles. Overall, this study sheds light on the genetic diversity and historical dynamics of these fascinating yet understudied populations, highlighting their importance in deepening our understanding of human evolution and adaptation to different environmental conditions.